Effect of surface plastic deformation of drill pipes material on their technological properties - Nikolay A. Buglov; Pavel S. Pushmin (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The need to study the effect of surface plastic deformation of drill pipes on their technological properties, which will significantly reduce the irrational material and energy costs of drilling wells, as well as optimize the technical and economic indicators of drilling operations. Aim. To increase the productivity of geological exploration by optimizing the operational characteristics of drill pipes. Objects. Drilling well, drilling shell, drill string, shot blasting of pipes, surface plastic deformation. Methods. Specialized test benches have been developed and manufactured for conducting experimental studies; processing of experimental research data was carried out by the graphoanalytic method. Results. The paper introduces the results of the study of the effect of surface plastic deformation produced by means of shot-impact treatment of the surface of the drill pipe material on their technological properties. The conducted studies shown a significant effect of surface plastic deformation of drill pipes on their technological properties and operational characteristics. In particular, it was found that microcracks and other microdefects can lead to a decrease in the strength and fatigue resistance of the pipe, as well as to a deterioration in its corrosion resistance. Conclusions. The optimal degree of surface coating of LBTN-54 and SBT-42 drill pipes, which guarantees a significant improvement in their technological properties, is close to 80%. With an optimal degree of surface plastic deformation of the material of LBTN-54 drill pipes the stiffness of their cross-section increases by 1.8 times; torsional stiffness increases by 1.3 times; damping capacity increases by 33%, and the amplitude of free vibrations decreases by an average of 1.9 times; power costs for turning them around their curved axis increase by 15%. At the optimal degree of surface plastic deformation of the SBT-42 drill pipe material the stiffness of their cross-section increases by 1.43 times; torsional stiffness increases by 1.4 times; damping capacity increases by 25%, and the amplitude of free vibrations decreases by an average of 1.75 times; power consumption for turning around its curved axis decreases by 7%. Surface plastic deformation of the LBTN-54 drill pipe material contributes to the expansion of the areas of their operation in the well in the mode of direct precession, which ensures the improvement of technical and economic indicators of drilling in difficult geological conditions.